Omega (?) Advancement Flap: A Circular Flap Design for the Aesthetic Closure of Circular Skin Defect - Arpaci, Enver; Altun, Serdar; Ertas, Nilgun Markal; Uysal, Ahmet Cagri; Inozu, Emre (Springer, 2017)
Background Most skin defects that require reconstruction with a local skin flap have a circular-or oval-shaped pattern. The majority of the skin flaps are planned in an angled shape. Therefore, it may be necessary to modify the shape of the defect or the distal flap border to minimize tissue distortion. We have designed a circular-shaped advancement flap to be compatible with the circular defect. Methods Eighteen cases of reconstruction of skin defects in the face, chest wall, hand and buttock area were performed using the omega advancement flap between 2010 and 2014. In this technique, a circular-shaped flap that has an equal diameter with the defect is planned adjacent to the defect. To facilitate the advancement of the flap and to avoid standing cones, deepithelialized equilateral triangular flaps are designed on both sides of the main circular flap. The circular flap is easily moved to the defect by pulling of the triangular flaps with minimal tension. Results All flaps survived without complication such as infection, hematoma or flap necrosis. No secondary surgery was required to correct contour deformities such as standing cones and trap-door deformities. The results were satisfactory aesthetically and functionally. Conclusions The omega advancement flap is an easy and reliable procedure for reconstruction of circular skin defects located on various anatomical regions.
Keywords: Circular defect; Local skin flap; Advancement; Omega